Nitrogen mineralization of legume residues: interactions between species, temperature and placement in soil - Miguel Oliveira; Dragan Rebac; João Coutinho; Luís Ferreira; Henrique Trindade (Spanish Journal of Agricultural Research, 2020)
Aim of study: To assess the interactive effects of legume species, residue placement and temperature on the net nitrogen (N) mineralization dynamics in a sandy loam soil.